Selective reduction of CO2 to a tantalum formate complex and release of methyl formate from the tantalum(V) center - Mörsdorf, Jean-Marc; Ballmann, Joachim (Inorganic chemistry, 2021)
A cyclometalated NHC-coordinated hydrido tantalum alkoxide was found to selectively react with CO2 to afford the genuine tantalum formate (NHC)(HCOO)Ta(ORF)3 with ORF = OC(CF3)2CH3. In the solid state, the presence of a κ2-O,O-formate moiety was established by single-crystal X-ray diffraction and ATR-IR spectroscopy, while NMR experiments and DFT modeling studies suggest that the κ1-O-coordination mode is preferred in solution. Despite the accessibility of the latter κ1-O-formate in solution, no over-reduction to a dinuclear methylene diolate was observed. Upon treatment with MeOTf, the κ1-O-formate was methylated selectively, which led to the formation of a tantalum triflate complex along with methyl formate. This is a rare example in which a value-added oxygen-containing organic product (here HCOOMe) is released from an oxophilic early transition metal (here TaV).
Gesehen am 22.03.2022
Im Titel ist die Zahl "2" nach "CO" tiefgestellt